Radioiodinated dechloro-4-iodofenofibrate: a hydrophobic model drug for molecular imaging studies - Breyer, Sandra; Semmler, Angelika; Miller, Tobias; Hill, Alexandra; Geißler, Simon; Haberkorn, Uwe; Mier, Walter (International journal of pharmaceutics, 2012)
Radiolabeling is a valuable option for tracking drug molecules in biodistribution experiments. In the development of innovative drug delivery systems the influence of the pharmaceutical formulation on the drugs’ pharmacokinetics has to be investigated. The hypolipidemic agent fenofibrate is an ideal model drug for testing the performance of drug delivery systems designed for poorly soluble compounds. Herein, we report a de novo synthesis of a fenofibrate derivative, dechloro-4-iodofenofibrate, as well as its conversion into its radioiodinated derivatives containing 125I or 131I. The enzymatic stability of the radiolabeled compounds synthesized was determined in vitro. A scintigraphic imaging study supplemented by biodistribution experiments and analysis of excreted metabolites revealed the stability required for in vivo applications and its similarity to fenofibrate. Therefore a convenient method is presented to synthesize radioiodinated derivatives of fenofibrate. These tracers show excellent in vitro and in vivo properties to study the behavior of lipophilic drugs.